Integration of knowledge in restaurants through multicriteria analysis for decision making - León Santiesteban, Martín; Larrañaga Núñez, Ana María (Unidad Editorial UPTC, 2020)
Abstract Knowledge is an intangible good of the organization that generates innovation, competitive advantage and efficiency, which is why necessary its permanent management and measurement supported with tools such as multicriteria analysis for decision making. In the restaurant companies located in the tourist destination of Mazatlan, Sinaloa, Mexico, innovation activities were carried out that integrate knowledge by free access sources, purchase and cooperation and that include a series of categories, so the objective is to identify the decision alternative for the integration of knowledge through a multi-attribute method in process innovation. The method used is the simple additive weighting approach, which through the case study led to the selection of alternatives, to the calculus of the performance matrix and the ranking of alternatives. In the findings, an order was made, and three restaurants stand out that better achieved the integration of knowledge and technology of the global result and in the individual the tendency to use sources of free access. In conclusion, since it is difficult to imitate process innovation, it is relevant to study the knowledge decision alternatives and identify the management of this intangible resource in companies to differentiate in a growing market. Keywords: Knowledge, management, multicriteria analysis for decision making, restaurant. JEL Codes: I210, M100, C6, Z300 Received: 27/02/2019. Accepted: 28/04/2020.  Published: 24/05/2020